(untitled) (International Journal of Irrigation and Water Management, 2014)
Irrigation development is a gateway to increased agricultural, water and land productivity, increased household and national food security. However, irrigation development has been a major challenge in many developing countries, including Egypt. The overall objective of this study is to detect the influence of different irrigation systems on water-use efficiency, crop and soil salinity in highly soil salinity. Two techniques were applied in experiment, the first technique was siphon irrigation, and the second one was gated pipe. The monitored parameters were water table depth, water and soil salinity and crop yield. The study revealed that the intensive management is a very important aspect for the success of siphon technique and cotton crop yield was higher by 17% compared to gated pipe irrigation treatment. The total soil salinity increased in both treatments. The siphon method increases the average salinity by 2.7% while the gated pipe increased it by 12.9%; converging the value of the crop coefficient in all relations used in most stages of growth, except Penman relationship which gave the highest values.